Identification of Growth Constraints in North Sumatra: A Growth Diagnostics Approach: Universitas Indonesia, Bappenas - Purwoharyono, Doddy; Sari, Sasmita Kartika; Ramadhan, Hafid Wahyu (IPB University, 2025)
North Sumatra economy is one of the highest contributors to the regional economy of Sumatra. The declining long-term growth trend of North Sumatra needs to be diagnosed so that a sustainable long-term economic growth can be achieved. This study focuses on analyzing binding constraint to investment and growth in North Sumatra using the HRV (Hausmann et al., 2005) growth diagnostic framework. The application of the HRV growth diagnostic framework in this study uses the benchmark method. To benchmark North Sumatra with other comparable regions, the hierarchical cluster method is used based on the characteristics of GRDP per capita, Total Population, Area, and Population Density. The benchmarking results found that government failures, especially micro risks including ease of doing business, low access and certainty of land ownership, high transaction costs, high levels of corruption and crime are the main obstacles to investment and economic growth in North Sumatra.